Pengaruh Loan To Deposit Ratio (LDR) Dan Rasio Biaya Operasional Pendapatan operasional (BOPO) Terhadap return on asset (ROA) (Studi Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2013) - Arja, Dharis Budhi; , Kusdiyanto, SE, MSi (2016)
This study aims to 1) determine the effect Loan To Deposit Ratio (LDR) and Operating Expenses Operating Income (ROA) to Return on Assets (ROA). 2) determine among Loan To Deposit Ratio (LDR) and Operating Expenses Operating Income (ROA) which variables are the dominant influence on the Return on Assets (ROA) Populations that are objects of this study are all listed banking companies (listed) in Indonesia Stock Exchange 2010-2013. The samples used were 23 commercial banks listed on the Indonesia Stock Exchange. Samples were taken by purposive sampling with certain criteria, namely the Bank issued financial statements for four years, ie the year 2010-2013, as well as the bank that has issued annual financial statements for the period 2010-2013. The method used in this research is by using multiple linear regression analysis to test the hypothesis that the t test and F test Before using multiple linear regression analysis, performed classical assumption beforehand. The conclusion of this study were 1) Loan to Deposit Ratio (LDR) and the ratio of Operating Expenses / Operating Income (ROA) have a significant effect on profitability (ROA), either individually or simultaneously. 2) The ratio of Operating Expenses / Operating Income (ROA) gives a greater influence than the Loan to Deposit Ratio (LDR). The value of the coefficient of determination (Adjusted R Square) of 0.860 means that 86.0% of variation Return On Assets (ROA) can be explained by two independent variables Loan to Deposit Ratio (LDR) and the ratio of Operating Expenses / Operating Income (ROA).